2016
DOI: 10.1002/ceas.12036
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Jyoti Meditation on Stress and the Moderating Role of Emotional Intelligence

Abstract: The authors examined whether Jyoti meditation (JM), a spiritually based meditation (Singh, 2012), influenced student counselors' (N = 60) level of stress and emotional intelligence (EI). Results from a randomized controlled trial and growth curve analysis provided a multilevel model in which JM reduced stress and EI moderated the effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…With regard to the experiences of mental health counselors and counselors‐in‐training, research supports the notion that an individual's level of EI may play a role in determining his or her resiliency to burnout (Gutierrez et al, , ; Gutierrez & Mullen, ; Testa & Sangganjanavanich, ). In a recent study, counselors‐in‐training with higher levels of EI reported lower scores of emotional exhaustion and depersonalization, indicating that EI serves an important role in counselor burnout (Testa & Sangganjanavanich, ).…”
Section: Emotional Intelligencementioning
confidence: 79%
See 1 more Smart Citation
“…With regard to the experiences of mental health counselors and counselors‐in‐training, research supports the notion that an individual's level of EI may play a role in determining his or her resiliency to burnout (Gutierrez et al, , ; Gutierrez & Mullen, ; Testa & Sangganjanavanich, ). In a recent study, counselors‐in‐training with higher levels of EI reported lower scores of emotional exhaustion and depersonalization, indicating that EI serves an important role in counselor burnout (Testa & Sangganjanavanich, ).…”
Section: Emotional Intelligencementioning
confidence: 79%
“…There is a growing body of literature that highlights the important role of EI in stress management and in the prevention of negative stress-related outcomes, such as burnout (Gutierrez, Conley, & Young, 2016;Karimi, Leggat, Donohue, Farrell, & Couper, 2014;Ullrich, Lambert, & McCarthy, 2012). EI is negatively correlated with perceived stress and physiological responses to stress and positively associated with adaptive coping strategies (S. K. Johnson & Blanchard, 2016;Mikolajczak & Luminet, 2008;Mikolajczak, Roy, Luminet, Fillée, & de Timary, 2007).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Specifically, Leppma and Young () conducted a 6‐week experimental trial with 103 master's‐level counseling students using a compassion‐based meditation that demonstrated significant increases in students' cognitive empathy and a significant relationship between quantity of meditation and treatment outcomes. Gutierrez et al () had similar success using a randomized controlled trial with counseling students that resulted in significant decreases in stress. Because of the level of stress and emotional exhaustion accompanying the work of counseling, researchers have expressed a need for student counselors to identify and apply self‐care strategies that can address stress, sustain empathy, and prevent burnout (Roach & Young, ).…”
mentioning
confidence: 95%
“…It is a meditation of looking. The mantra is intended to direct attention toward an inner spiritual connection and away from negative thoughts, emotions, and the physical body or sensations (Gutierrez, Conley, & Young, ; Michalsen et al, ; Singh, ). In JM, participants choose a mantra that has a spiritual meaning, close their eyes, and shift attention from thoughts to a centered point behind and between the two eyebrows (Michalsen et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation